A Novel Parallel Viterbi Decoding Scheme for NoC‐Based Software‐Defined Radio System. Issue 5 (1st October 2013) - Wang, Jian; Li, Yubai; Li, Huan
Abstract : In this paper, a novel parallel Viterbi decoding scheme is proposed to decrease the decoding latency and power consumption for the software‐defined radio (SDR) system. It implements a divide‐and‐conquer approach by first dividing a block into a series of subblocks, then performing independent Viterbi decoding for each subsequence, and finally merging the surviving subpaths into the final path. Moreover, a network‐on‐chip‐based SDR platform is used to evaluate the performance of the proposed parallel Viterbi decoding scheme. The experiment results show that our scheme can speed up the Viterbi decoding process without increasing the BER, and it performs better than the current state‐of‐the‐art methods.